Pengelolaan Desa Mandiri Pangan Berbasis Ekonomi Lokal Untuk Mewujudkan Ketahanan Pangan Kota Batu - Alfi Qodrun Nada (Departemen Ilmu Pemerintahan Fisip Unhas, 2020)
The Batu City Food Self-Reliance Program was motivated by problems, the number of households with poor families above 30% according to the survey results of the Batu City BPS Team. The establishment of the food self-sufficient village program. The aim of the food self-sufficient village program has a goal to overcome poverty and reduce the level of food insecurity so that it will improve the welfare of the community and business activities are able to create income and employment opportunities that as a driver of economic growth for the community. The purpose of this study was to determine the management of the local economy-based independent village food in realizing food security in the city of Batu and its problems in trying to achieve food security of the poor in Batu City. The method used in this research is descriptive qualitative. The theory used in this study is the local economy that was coined by Blakely and Bradshaw and management to realize food security in Batu City. Whereas in its management the Batu City Food Security Service uses methods which include Planning, Organizing, Implementing and Evaluating. In its implementation there are several stages that must be done including. The first stage is the preparation stage. Second is the growth stage, the third stage of development and finally the independence stage. Currently in Batu the implementation has gone through the four stages of the program, namely conducting a sustainable program for the food self-sufficient village program.